Optimalisasi Penggunaan Sumber Daya Manusia dalam Meningkatkan Efisiensi Prouksi Pertanaian di Desa Rensing: Optimizing the Use of Human Resources to Increase Agricultural Production Efficiency in Rensing Village - Sirajun Nasihin; Suparlan; Karman Salmankan; M. Taufik Ansyori; Tomi Kurniawansah (Pendidikan Al-Gafari, 2026)
The agricultural sector plays a vital role in the national economy, yet its productivity still faces various challenges. One major obstacle is the suboptimal utilization of human resources (HR) in this sector. This study aims to analyze how optimizing the use of human resources can improve the efficiency of agricultural production in Rensing Village, West Sakra District, East Lombok Regency. This study uses a qualitative approach with data collection methods through interviews, observations, and documentation. The results of the study show that farming experience, length of education, age, and participation in extension have a significant role in the productivity and efficiency of farming businesses. Farmers who have long experience are better able to overcome technical problems in the field. However, the low level of education and lack of participation in counseling are obstacles in the adoption of new technologies. In addition, the dominance of elderly farmers is also a challenge in modern agricultural management. Therefore, improving the quality of farmer human resources through education, farmer regeneration, and extension intensification is needed to create a more efficient and sustainable agriculture.